Dampak Industri Pariwisata Terhadap Penyerapan Tenaga Kerja Ditinjau dari Perspektif Ekonomi Islam (Studi pada Hotel, Biro Perjalanan Wisata, Kuliner dan Objek wisata Kabupaten Lombok Barat) - Romi Putra Saroji (Fakultas Ekonomi dan Bisnis Islam Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2018)
Tourism in west lombok region had inreased from years. This situation gives more beriefets in tourism such as hotel,food and beverage,and travel. Agency which also gives more opportunitres to cleate more employee. This research aims to finds out the hotel influences, trevel agency,food and beverage and tourism spot lite to the new employee absorption in west lombok, also this new employee absorption in this variable has been viewed from the islamic perspective. This research was a quantitatif research with a random variabel such as, hotel,trevel agency, food and beverage and the new employee absor ption. The data analysis has been done by as double regression test. The result showed that hotel, food and beverage(hotel), and trevel agency has constant result so that the new employee absorption increasedto be 2283,923. For hotel variabel is it increased for about 1% so that the new employee absorption also will increased to be 48,233 food and beverage hotel which increased 1% also showed thatthe new employee will also incresed to be 0,021 of herwise trevel agency, if it increased 1% so that the absorpation of the employee will increased ,717. In the hotel,food and beverage (restaurant). Trevel agency showed there is a absopation of the employee. This situation can be seen in how many employee since 2010-2015 which more increased for each variable.